PEMBENTUKAN KARAKTER SISWA MELALUI KETELADANAN KEPALA SEKOLAH DAN GURU PENDIDIKAN KEWARGANEGARAAN - Triwantoro Triwantoro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2019)
This study aims to reveal the formation of character through the example of the Principal and the Citizenship Education Teacher in SMA 1 Subang. This research is a descriptive study with a qualitative approach. The research subjects were the Principal and Citizenship Education Teacher at SMA 1 Subang. Data collection using interview, observation and documentation techniques. Checking the validity of the data is done by source triangulation. Data analysis is done qualitatively through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the Principal and Citizenship Education Teachers in SMA Negeri 1 Subang formed student character through exemplary speech, personality traits, attitudes and appearance that were in accordance with religious character, discipline, democracy, nationalism, love of the country, peace of mind , care for the environment, and care for the social.